TINJAUAN KRITIS ANGGARAN KETAHANAN PANGAN DAN IMPOR KOMODITAS BERAS MENURUT PERATURAN PERUNDANG-UNDANGAN - Achmadudin Rajab Rajab (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2023)
Even though the food security budget has increased, the rice commodities supply has always depended on imports. Therefore, this study aims to analyze the relationship between the food security budget and rice imports and harvested area. The research method used is quantitative research with Spearman correlation. The data used are secondary data, namely the food security budget, rice prices, rice imports, harvested area, productivity, and production of rice commodities. The study results show that the food security budget has a negative and insignificant relationship to rice imports and harvested area. Second, the food security budget has a positive and insignificant relationship to rice prices and rice production. Third, rice imports have a negative and insignificant relationship to rice prices. Fourth, data disputes between government agencies in determining rice import policies are still occurring. Therefore, the government needs to make efforts, namely first, the urgency of the food security budget for an even distribution of increased productivity. Second, is the government’s urgency to map the distribution of rice production capacity.